Pengaruh Pengalaman Kerja, Kesejahteraan Kerja Dan Beban Kerja Terhadap Produktivitas Kerja Karyawan Bagian Departemen Perawatan Unit Pt. Satria Bahana Sarana - Molvy, Ryan; Hardiansyah, Hardiansyah; Aprini, Nisma (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This research aims to determine and analyze the influence of work experience, work welfare, and workload, individually and collectively, on employees' work productivity in the PT Unit Maintenance Department. Satria Bahana Sarana. The research method used in this research is a quantitative method using questionnaires distributed to respondents. Test data quality using validity tests, reliability tests, and normality tests. The descriptive and inferential analysis used statistical calculations with multiple regression formulas, partial tests, simultaneous tests, and coefficient of determination. The study results showed that work experience, welfare, and workload significantly affected employees' work productivity in the PT Unit Maintenance Department. Satria Bahana Sarana